Accuracy of face castings employing thermoplastic custom trays for facial molding - Kaue Campos Pavanello; Priscila Galzo Marafon; Beatriz Silva Câmara Mattos (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the dimensional stability of a new facial molding technique using thermoplastic custom molding tray. Methods: The designs established demarcation of facial anthropometrics landmarks, making linear measurements with a digital caliper. Facial molding was carried out using thermoplastic custom trays, constructing a facial plaster cast with the anthropometric landmarks already transferred by measuring the linear dimensions on the plaster cast and statistical analysis. Results: All linear measurements in the palpebral and labial regions presented statistically significant distortions. Only one of the linear measurements from the orbital region did not demonstrate any significant distortion. The nasal region presented the least amount of distortion. Conclusions: Although statistically significant, distortions were due to the method of breathing and were considered to be clinically irrelevant. The reduction in the working time, the comfort provided to the patient and the dimensional accuracy of the plaster cast obtained by the facial molding technique using custom perforated molding tray suggest that this technique should be employed for making facial prostheses.